EVALUASI KEBERHASILAN SISTEM TERINTEGRASI SIPD – SIMPAD DALAM PENGEMBALIAN BELANJA DAERAH - Pratiwi, Febby Reysa Dian; Miftah, Ahmad Zaini (JURNAL LENTERA BISNIS, 2026)
This study was motivated by the fact that the expenditure reimbursement process is still carried out manually and through two separate systems, namely SIPD and SIMPAD, which require repeated data input and result in a slow validation process. This study aims to analyze the success of SIPD-SIMPAD integration based on user perceptions of efficiency and accountability using the DeLone & McLean Model. It uses a qualitative method with a case study approach through interviews and observations of system users in the DKI Jakarta Provincial Government environment. The results show that system integration has a positive impact on efficiency, data accuracy, transparency, and accountability. The system is considered easy to use, fast, and stable, with technical support that helps users adapt. The success of this integration reflects how technology, organizational support, and human resource readiness complement each other and form a new, more efficient and adaptive work pattern in the government environment.